Peningkatan Hasil Belajar Matematika Melalui Penerapan Media Pembelajaran Tiga Dimensi - Dewi Elisa Amaliyah; Abd Aziz; Farich Purwantoro (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2023)
The purpose of this study is to determine the application of three-dimensional media to improve learning outcomes, to determine the results of learning mathematics using the application of three-dimensional media learning, to determine the supporting factors and inhibiting factors in the application of three-dimensional media. The research method used is to describe data as words, pictures, and not as numbers. The data collection technique used is the method of observation, interviews and documentation with data analysis used in the analytic descriptive analysis method in the form of words and not pictures. The results of the study found that the use of three-dimensional learning media helped improve mathematics learning, where student learning outcomes which were initially 60% experienced an increase of 13%, namely 73%. This increase can be seen through the learning method using three-dimensional media which can make it easier for students to know examples of geometric objects directly, this makes students' mindsets faster in understanding geometric material.